Motility and viability of ram sperm cryopreserved in a Tris-egg yolk extender supplemented with anti-oxidants - Maia, Marciane da Silva; Bicudo, Sony Dimas [UNESP]; Azevedo, Hymerson Costa; Sicherle, Carmen Cecilia [UNESP]; de Sousa, Daniel Bartoli [UNESP]; Rodello, Leandro [UNESP] (Elsevier B.V., 2009)
The objective of this study was to evaluate the effects of the addition of the anti-oxidants Trolox and catalase to a ram semen cryopreservation extender, on the basis of post-thaw sperm motility, plasma membrane integrity, acrosomal membrane integrity and mitochondrial membrane potential. Semen from 23 Santa Ines rams was collected using an artificial vagina, and one ejaculate from each ram was evaluated and included in the study. Semen samples were diluted to a concentration of 400 x 10(6) cells/ml in Tris-egg yolk extender (control) or the same extender supplemented with 50 mu M Trolox/10(8) sperm (TRO), 50 mu g catalase/ml (CAT) or a combination of Trolox and catalase (TROCAT). The semen was loaded into 0.25 nit straws, cooled and frozen in a programmable freezer and subsequently stored in liquid nitrogen. Frozen straws were thawed in a water bath for sperm evaluation. Post-thaw sperm motility characteristics were determined by CASA, and plasma membrane integrity, acrosome integrity and mitochondrial membrane potential were assessed using PI/FITC-PSA/JC-1 probes. Total sperm motility was significantly higher (P<0.05) in the control (72.0 +/- 1.5%) and in the samples in which catalase was included in the extender (CAT = 69.0 +/- 1.5%), compared to samples containing only Trolox (TRO = 65.0 +/- 1.5%) or Trolox in combination with catalase (TROCAT = 61.0 +/- 1.5%). Progressive motility was significantly (P<0.05) higher in the CAT extender (31.0 +/- 1.0%) than in the TRO (26.0 +/- 1.1%) and TROCAT (27.0 +/- 1.1%) supplemented extenders. Catalase supplementation resulted in a significantly (P<0.05) higher percentage of viable sperm (35.5 +/- 1.3%) following cryopreservation, than the control (29.9 +/- 1.3%) and TROCAT (28.1 +/- 1.3%) supplementation. Anti-oxidant supplementation did not improve mitochondrial activity. The total number of sperm showing a high mitochondrial membrane potential was low in all treatments. The percentage of viable sperm was positively related with total sperm motility, progressive motility and rapid movement, while a negative correlation was observed with the percentage of slow and static sperm. Results indicate that supplementation of the extender with the anti-oxidant catalase improves sperm viability and, to a lesser extent, the progressive motility of ram sperm after cryopreservation in a Tris-egg yolk extender. (C) 2009 Published by Elsevier B.V.
Keywords: Catalase; Trolox; Plasma membrane integrity; Mitochondrial membrane potential; Ram semen; Anti-oxidants